Herald of New, Healthier Mode of Life (Academization of Physical Education and Formation of The Faculty of Sport in Slovenia) - Tomaž Pavlin; Milan Žvan (Karolinum Press, 2015)
In the period between the two World Wars, physical education became an important educational sphere in Yugoslavia and Slovenia. At the same time, the process of giving the educational sphere a Slovene character has to be emphasized, which was ensued by the establishment of a new Southern Slav state. In this process, physical education was professionally influenced by Sokol gym and Sokol education. At the same time, the Sokol started the process of the formation of a state regulated short-cycle college of physical education. Behind the action were demands for professional teachers and coaches. The process culminated after the Second World War with the establishment of the Institute of Physical Education in Ljubljana (1953). The Institute adopted Sokol gym as a basic physical activity but it was soon reorganized and renamed 3-year Short-cycle College of Physical Education and finally in 1960, 4-year College of Physical Culture, which was the beginning of the present Faculty of Sport. This paper discusses the historical progression of physical education to academic science on the basis of the development of the Faculty of Sport and on the basis of available historical primary sources and professional texts.